Socio-demographic and maternal health indicators of inhibitory control in preschool age children: evidence from Growing Up in New Zealand. (1st April 2020) - Buckley, Jude; Peterson, Elizabeth R.; Underwood, Lisa; D'Souza, Stephanie; Morton, Susan M.B.; Waldie, Karen E
Abstract : Inhibitory control is central to developmental trajectories of cognitive, emotional and social functioning in children. Here, inhibitory control was measured using the Luria hand clap task (an adapted version of the Luria pencil tap task). A sample of 5, 448 children age 4½ years and their mothers from a longitudinal, population-based New Zealand cohort were included in this study. Antenatal maternal health indictors, child characteristics and performance on the Luria hand clap task were assessed using multivariate ordinal logistic regression. Seven covariates, including mother's ethnicity and education, and child's gender, age and birthweight were included. Based on Luria task performance scores that approximated the 25th and 50th percentiles, children were categorised into three groups (low, intermediate, high). High Luria task performance was associated with maternal relationship status, maternal education, first trimester folate supplementation, maternal BMI and smoking before pregnancy. In addition, children born heavier, and female, and older children were more likely to be in the top Luria score category relative to children born smaller, male and younger. A number of potentially modifiable maternal factors significantly predict Luria task performance in children age 4½ years. Identifying socio-demographic, child characteristics and maternal factors that are associated with inhibitory control is a crucial first step for identifying children at risk of atypical inhibition development and informing behavioural intervention strategies.